The integrated approach to traction calculation of belt conveyors - Goncharov K.A.; Dunaev V.P. (Научно-технический вестник Брянского государственного университета)
There was suggested a probabilistic mathematical model of tractive effort distribution among the drives of multidrive belt conveyors. This model takes into account (in an inverted way) speed variations of different points of tractive and carrying belt forms using an artificial increase in probabilistic interval boundaries of slide departures of drive engines. Taking into consideration the given mathematical model, an integrated approach to traction calculation of belt conveyor of conventional construction and random configuration is formulated. This approach is based on presentation of units of the traction calculation process in the form of classifying characteristics with the corresponding mathematical description. The set of these classifying characteristics for each unique engineering case forms the corresponding specific equation systems of traction calculation.